IMMEDIATE EFFECTS OF STRUCTURED DEEP BREATHING ON CARDIOVASCULAR FUNCTION, AUTONOMIC REGULATION, AND PERCEIVED STRESS IN HEALTHY ADULTS - Mallipeddi Kalyani; Jyothi Ashok Kumar; Praveen Kumar Panuganti (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Deep breathing exercises are a simple, non-pharmacological technique shown to enhance autonomic balance, improve cardiovascular function, and reduce psychological stress. However, evidence on the acute effects of short-term, structured deep breathing in healthy adults remains limited. This study aimed to evaluate the impact of short-term deep breathing exercises on heart rate variability, blood pressure, respiratory function, oxygen saturation, and perceived stress.Methods: A total of 100 healthy adults were randomly assigned to two groups: a Control group (n = 50; no specific intervention) and an Experimental group (n = 50; performed a standardized deep breathing protocol). Physiological parameters including systolic and diastolic blood pressure, heart rate, heart rate variability (RMSSD), respiratory rate, and oxygen saturation were measured at baseline and post-intervention. Psychological stress was assessed using the Perceived Stress Scale (PSS). Independent and paired t-tests were used for between- and within-group comparisons, respectively, with significance set at p < 0.05.Results: At baseline, both groups were comparable across all parameters. Following the intervention, the experimental group demonstrated significant reductions in systolic blood pressure (–5.28 mmHg, p = 0.0045), diastolic blood pressure (–4.06 mmHg, p = 0.0025), heart rate (–4.28 bpm, p = 0.023), and respiratory rate (–2.03 breaths/min, p < 0.0001). Heart rate variability improved markedly (RMSSD: +8.39 ms, p = 0.0001), and oxygen saturation increased (+0.93%, p < 0.0001). A significant reduction in perceived stress was also observed (–4.79 points, p < 0.0001). No significant changes were found in the control group.Conclusion: Short-term deep breathing exercises produced measurable improvements in cardiovascular regulation, autonomic balance, respiratory efficiency, and psychological well-being among healthy adults. These findings highlight the potential of brief, structured deep breathing as an effective, low-cost, and accessible strategy for promoting holistic health in everyday life.